(untitled) (International Journal of Ayurveda and Pharma Research, 2019)
Ayurveda is the Ancient system of Medicine which gives equal importance to preventive and curative aspects of treatment. Rasayana Chikitsa plays a key role in the treatment of all the diseases (both in curative and preventive). There is nothing painful and stressful to women, for not being conceived. In the present modern era, female infertility is raised to the alarming extent due to diet & lifestyle modifications. Couples suffering from the infertility are approaching the infertility centres and going for the artificial reproductive techniques (IUI, IVF, ICSI-ET, Sarogasy). Ayurveda, through its unique line of treatment approaches, paves the way for fertility management through the medicines along with diet & lifestyle modifications. The Commonest cause for fertility being the Hypothyroidism in females (in this present study, I have considered hypothyroidism as Rasa pradosaja vyadi), clinical study was done at OPD, DR. BRKR Govt Ayurvedic College, Hyderabad and treated the patient with Dipana, Pachana, Rasayana Chikitsa and the patient conceived. In this present article an attempt is made to review and understand the concept of Rasayana chikitsa in the management of infertility with special reference to hypothyroidism (Dhatupradosja vyadi).